MANFAAT MEDIA PEMBELAJARAN DALAM PEMEROLEHAN BAHASA KEDUA ANAK USIA DINI - Jayanti Swastyastu, Luh Tri (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
Early childhood has a unique personality. Children have a high curiosity, and become good imitators in their daily life through stimulus with their senses. It indicates the child's growth and development normally. One of them is the ability to speak from their birth as a communication tool. The first language of a child is the mother language or language used daily in the family and also the surrounding environment. As their development, children gain knowledge using second, third language, and so on. A second language acquisition in children will be more effective by using learning media. The media is used to deliver messages from the sender to the addressee so that it stimulates the child's thoughts, feelings and attention. In terms of the second language acquisition of the child, appropriate media for children's effectiveness in achieving language acquisition are grouped into three major groups, namely: 1) Visual Media, 2) Audio Media, and 3) Audiovisual Media. Visual media are media in the form of images and tend to use the sense of sight, be it unmoved object or miniature object. While audio media is a media that relies on childrenâ€™s additives (hearing). Audiovisual media is a combination of visual media and audio media which is better known as video. This learning media is able to stimulate childrenâ€™s stimulus in acquiring a second language significantly.Â